ГЕНОТОКСИЧЕСКОЕ ДЕЙСТВИЕ ФИПРОНИЛА НА КРЫС РАЗНОГО ВОЗРАСТА (Experimental biology, 2009)
Mutagenic activity of fipronil on animals of different age groups under acute and sub-acute exposure was investigated. It was established genotoxic effect of fipronil. Its degree depended on exposure time and animal’s age.
Keywords: Mutagenic activity